Hubungan Lama Penggunaan Kontrasepsi Suntikan Dengan Hipertensi - Susiloningtyas, Is; Ediyono, Suryo (Malang Journal of Midwifery (MAJORY), 2023)
Indonesia is a country that has a high population density. According to data from the Central Statistics Agency (BPS) in 2010, Central Java Province ranks third with a population of 32,382,657 people. Injectable contraceptives, the most widely used are contraceptive drugs that aim to prevent pregnancy where the raw material contains estrogen and progesterone preparations. According to data from the National Family Planning Coordinating Board (BKKBN), the most injection family planning users in Central Java were compared to other contraceptive methods, reaching 914,544 people. One of the concerns of using injection contraceptive methods are hypertension. This research was a non-experimental study which was a descriptive analytic study with a cross sectional approach. The population in this study were all injection family planning acceptors who came to the midwife Syarifah Mranggen Demak, a sample of 30 people.The results of the study, which were obtained from 30 people, showed that the majority of mothers who used injectable contraceptive contraception were women aged 36-40 years, namely 19 people (29.2%), that the duration of using injection contraception was between 3-5 years 30 people (46.1%), blood pressure acceptors with injection contraception was normal as many as 61 people (93.8%) and those who had hypertension were 4 people (6.2%). Mothers who use family planning injection acceptors who experience an increase in blood pressure are 5 people who have used injection contraception more than 8 years and aged 36-40 years and there is no relationship between the length of contraception use and hypertension